Global self‑rating of oral health as summary tool for oral health evaluation in low‑resource settings (2015)
Global Self‑Rating of Oral Health (GSROH) has numerous benefits, especially in resource constrained environments with a paucity of dentists thereby potentially limiting administration of oral health surveys and monitoring of dental treatment. The aim of the study was to identify factors that could influence or predict poor self-ratings of oral health. The study was descriptive in design. Data were collected using structured interviewer administered questionnaire, which had items on socio‑demographic characteristics of the respondents and their GSROH. Oral examination was conducted to identify untreated dental caries, missing teeth, and mobile teeth. Data were analyzed using SPSS, and the P value was set at 0.05. There were 600 participants; 400 were teachers constituting the non‑patient population and 200 were dental patients with age ranging from 18 to 83 years. A total of 169 (28.1%) participants rated their oral health as poor, including 104 patients (52.0%) and 65 (16.2%) non‑patients (P < 0.001). Having had toothache in the preceding 6 months (62.4% vs. 16.0%, P < 0.001), mobile teeth (46.7% vs. 24.2%, P <0.001), decayed teeth (49.0% vs. 21.3%, P < 0.001), missing teeth (35.0% vs. 26.1%, P =0.042), or DMFT score greater than zero (41.1% vs. 20.7%, P < 0.001) was associated with poor GSROH. Presence of mobile teeth [odds ratio (OR) = 2.68; 95% confidence interval (CI):1.29, 4.23; P < 0.001] and carious teeth (OR = 2.25; 95% CI: 1.09, 4.65; P = 0.029) were independent predictors of GSROH. Conclusion: The GSROH was able to identify individuals with or without oral conditions in the studied population, and thus may be used in oral health surveys to assess the oral health status and in monitoring of treatment outcome